2015
DOI: 10.1093/jee/tou035
|View full text |Cite
|
Sign up to set email alerts
|

Lambda-Cyhalothrin Resistance in the Lady Beetle Eriopis connexa (Coleoptera: Coccinellidae) Confers Tolerance to Other Pyrethroids

Abstract: Pyrethroid insecticides are widely recommended to control insect defoliators but lack efficacy against most aphid species. Thus, conserving aphid predators such as the lady beetle Eriopis connexa (Germar) is important to pest management in crop ecosystems that require pyrethroid sprays. In a greenhouse, early fourth-instar larvae and 5-day-old adults from susceptible (S) and resistant (R) E. connexa populations were caged on lambda-cyhalothrin-treated cotton plants, after which survival and egg production (for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…The field-collected insects were kept in plastic containers for adult rearing and egg collection, and late larvae and pupae were all reared as described in Torres et al . (2015). Rearing was conducted at the Biological Control and Insect Ecology Laboratory of the ‘Universidade Federal Rural de Pernambuco (UFRPE)’, and lady beetle colonies were maintained at 25 ± 2°C with a photoperiod of 12:12 h (L:D).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The field-collected insects were kept in plastic containers for adult rearing and egg collection, and late larvae and pupae were all reared as described in Torres et al . (2015). Rearing was conducted at the Biological Control and Insect Ecology Laboratory of the ‘Universidade Federal Rural de Pernambuco (UFRPE)’, and lady beetle colonies were maintained at 25 ± 2°C with a photoperiod of 12:12 h (L:D).…”
Section: Methodsmentioning
confidence: 99%
“…Most of these pest species are not targeted by pyrethroids. Pyrethroid formulations are widely recommended against defoliators (Agrofit, 2016); therefore, the mortality caused to pest populations by pyrethroids and E. connexa may be complementary (Spíndola et al ., 2013; Torres et al ., 2015). The remaining aphids not killed by pyrethroids and reduction of competition with other predators susceptible to pyrethroids (Torres & Ruberson, 2005), furnish prey, and free space to surviving lady beetles carrying alleles for resistance.…”
Section: Introductionmentioning
confidence: 99%
“…At least ten predator mites, which belong to Amblyseius genus, Phytoselulus genus and Pythlodromus genus, were confirmed to develop high resistance to 12 OPs, two CBs, and five Pyrethroids (Zhao et al , 2012). Among predator ladybirds, the resistances toward various insecticides were reported (Duan et al , 2002; James, 2003; Youn et al , 2003; Al-Doghairi et al , 2004; Yu et al , 2014; Li et al , 2015), e.g., Stethorus gilvifrons toward parathion-methyl and bifenthrin (Kumral et al , 2011), Eriopis connexa toward pyrethroid (Torres et al , 2015), and Listronotus maculicollis toward bifenthrin and bifenthrin combined with synergists affecting three detoxification systems (Ramoutar et al , 2009). But, no evolution and physiological mechanisms of the insecticide resistance in the predacious P. japonica were elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Among predatory species, it has been shown that the natural enemies could also develop resistance to insecticides corresponding to that in the pest insects ( Georghiou 1986 , Pathan et al 2010 , Sayyed et al 2010 , Alperkumral et al 2011 , Rodrigues et al 2013 , Torres et al 2015 ). The resistance to parathion-methyl and bifenthrin in Stethorus gilvifrons (Coleoptera: Coccinellidae) ( Alperkumral et al 2011 ) and to pyrethroid in Eriopis connexa ( Torres et al 2015 ) was reported. Elevated detoxification and insensitivity target were thought to be involved in resistance to insecticides in spider mites ( van Leeuwen and Tirry 2007 ).…”
mentioning
confidence: 99%
“…Multiple biochemical resistance mechanisms, including elevated carboxyestsrases (CarE) and GST activity and target-site insensitivity (insensitive acetylcholinesterase [AChE]) were involved in the resistance mechanisms in S. gilvifrons ( Alperkumral et al 2011 ). As compared with susceptible strain, insecticide-resistant E. connexa showed significantly higher survival rate ( Torres et al 2015 ). To study the role of detoxification enzyme in insecticide resistance, the synergistic effects of enzyme inhibitor, including piperonyl butoxide (PBO), diethyl maleate (DEM), or triphenyl phosphate (TPP), on chemical insecticides were studied in P. japonica or A. bipunctata ( Jansen et al 2010 ).…”
mentioning
confidence: 99%